Acetylcholinesterase, Specific Acetylcholinesterase and Total Protein Concentrations in the Brain Regions of Broiler Chickens Fed Dietary Monosodium Glutamate - Olumuyiwa Joseph Olarotimi; Imoleayo Sarah Oladeji; Olufemi Adesanya Adu; Francis Ayodeji Gbore (Turkish Journal of Agriculture: Food Science and Technology)
The study was carried out to examine the effect of varied levels of dietary monosodium glutamate on acetylcholinesterase, specific acetylcholinesterase and total protein concentrations in the brain regions of broiler chickens. Three hundred (300) day – old unsexed Abor – acre chickens were randomly assigned to diets: A, B, C, D, E and F containing 0.00, 0.25, 0.50, 0.75, 1.00 and 1.25 g/kg MSG respectively. Each treatment was replicated 5 times with 10 birds per replicate. The birds were fed ad – libitum and provided with clean water for 8 weeks (56 days) after which 2 birds per replicates were slaughtered. The brains were removed, dissected into different regions comprising of the olfactory lobe, pineal body, optic lobe, cerebellum and the medulla oblongata. The different parts of the brain were homogenized to determine the acetylcholinesterase and total protein which were also used in the assessment of the specific acetylcholinesterase of the brain. No significant differences were observed in the acetylcholinesterase activity of the olfactory lobe, pineal body, optic lobe, cerebellum except for the medulla. Likewise, the dietary monosodium glutamate did not influence the activities of the total protein and specific acetylcholinesterase of the olfactory lobe portion of the brain. The dietary monosodium glutamate exerted significant effects on the total protein of other brain parts studied and which invariably resulted in significant changes in the specific acetylcholinesterase of the optic lobe, cerebellum and medulla except for the optic lobe. This study revealed that monosodium glutamate added to broilers diet above 0.75 g/kg significantly altered the concentration of the brain acetylcholinesterase, total protein and specific acetylcholinesterase thereby impaired brain functions.